2020
DOI: 10.2337/dc19-1622
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Variation in Diabetes Screening Within an Integrated Health System

Abstract: Variation in diabetes screening in clinical practice is poorly described. We examined the interplay of patient, provider, and clinic factors explaining variation in diabetes screening within an integrated health care system in the U.S. RESEARCH DESIGN AND METHODSWe conducted a retrospective cohort study of primary care patients aged 18-64 years with two or more outpatient visits between 2010 and 2015 and no diagnosis of diabetes according to electronic health record (EHR) data. Hierarchical three-level models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…15 Previous research has also found that it tends to be clinical experience rather than guidelines that prompts screening 19 and that screening varies at the provider and the clinical level. 20 In the current study, we found that most of the centres that screened for prediabetes targeted people with other health problems, such as hypertension and obesity. Similar results have been found in other studies, 12,[20][21][22] where risk factors like polycystic ovary syndrome and highrisk ethnicity are not as well-recognised as the metabolic ones.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…15 Previous research has also found that it tends to be clinical experience rather than guidelines that prompts screening 19 and that screening varies at the provider and the clinical level. 20 In the current study, we found that most of the centres that screened for prediabetes targeted people with other health problems, such as hypertension and obesity. Similar results have been found in other studies, 12,[20][21][22] where risk factors like polycystic ovary syndrome and highrisk ethnicity are not as well-recognised as the metabolic ones.…”
Section: Discussionmentioning
confidence: 72%
“…There are few studies on screening for prediabetes in primary health care. [15][16][17][18][19][20][21] Most have been carried out in the United States (US), [15][16][17][18][19][20] where the health care system differs from the system in Sweden. One took place in Malta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some general practitioners in care groups diagnose and refer patients to the integrated care program earlier than general practitioners in other care groups. 44 Therefore, simply taking all the patients newly included in the integrated care program for DM2 reduces the comparability of care group populations, producing bias in the results. Our selection made the study population more homogeneous, and thus comparisons between the care group populations were fairer as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes screening tests considered in this study include FPG ≥ 7.0 mmol/l, OGTT ≥ 11.1 mmol/l, HbA 1c ≥ 48 mmol/mol, opportunistic RPG > 6.7 mmol/l and GCT > 8.9 mmol/l ( Table S1). The gold standard for diagnosing type 2 diabetes was either FPG ≥ 7.0 mmol/l or OGTT ≥ 11.1 mmol/l because recent evidence suggests most clinicians diagnose diabetes with a single positive test [16].…”
Section: Screening Testsmentioning
confidence: 99%